Defense Mechanisms and Treatment Response in Depressed Inpatients - de Roten, Yves; Djillali, Slimane; Crettaz von Roten, Fabienne; Despland, Jean-Nicolas; Ambresin, Gilles (Frontiers in Psychology, 2021)
The study investigated the extent to which defensive functioning and defense mechanisms can predict clinically meaningful symptomatic improvement within brief psychodynamic psychotherapy for recurrent and chronic depression in an inpatient setting. Treatment response was defined as a reduction in symptom severity of 46% or higher from the baseline score on the Montgomery–Asberg Depression Rating Scale. A subsample of 41 patients (19 responders and 22 nonresponders) from a randomized controlled trial were included. For each cases, two sessions (the second and the penultimate) of brief inpatient psychodynamic psychotherapy, a manualized 12-session therapy program developed in Lausanne, were transcribed and coded using the Defense Mechanisms Rating Scales (DMRS) and the Psychotic Defense Mechanisms Rating Scale (P-DMRS), an additional scale developed to study psychotic defenses. Results showed that defensive functioning and mature and immature defense changed during psychotherapy and predicted treatment response. The addition of psychotic defenses allows a better prediction of the treatment response. Overall, these results are in line with previous research and provide further validation of defensive functioning as a predictor of outcomes and a mechanism of change in psychotherapy.